MENINGKATKAN KETERAMPILAN PERMAINAN SEPAKBOLA MENGGUNAKAN METODE PEMBELAJARAN DEMONSTRASI PADA SISWA KELAS VI SDN 003 PULAU KOPUNG SENTAJO KECAMATAN SENTAJO RAYA - Indrawani Indrawani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
The problem that is often found in the learning process is low student learning outcomes. as found by researchers at SDN 003 Kopung, the average student learning outcomes that still cannot be said to be complete as a whole, therefore researchers tried to apply demonstration learning models to improve student learning outcomes. This study aims to improve the learning outcomes of PJOK students in football material. Classroom action research is an improvement in the learning process to solve the problems teachers get in class. Data obtained after research on teacher activities in the first cycle of the 1st meeting with a percentage of 50%, the second meeting with a percentage of 57%, in the second cycle at the third meeting percentage of 62.5%, and at the 4th meeting percentage obtained 80%. Student observation data in this study obtained the percentage of the first cycle of the first meeting of 45%, the second meeting was 52%, in the second cycle of the third meeting was 64%, and the fourth meeting has obtained a percentage of 84.5% prove that student activity has increased. Data on the improvement of student learning outcomes in class VI SDN 003 Pulau Kopung in the initial data obtained an average of 57, on the daily test I obtained a class average of 71, and in the daily test II obtained an average of 86. The conclusion of this study is that the use of demonstration methods is effective in class VI and can improve ability football